On the principles of English university education - Whewell, William, 1794-1866. (London : Routledge/Thoemmes Press, 1994)
This book is about on the Principles of the Subjects of University Teaching; of Direct and Indirect Teaching; and of Discipline.
Keywords: Education; Higher education; Universities and colleges; Universities and colleges -- Great Britain; Education, Higher -- Great Britain